2023
DOI: 10.14569/ijacsa.2023.0140616
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Enabled Mobile Chatbot Psychologist using AIML and Cognitive Behavioral Therapy

Abstract: In recent years, the demand for mental health services has increased exponentially, prompting the need for accessible, cost-effective, and efficient solutions. This paper introduces an Artificial Intelligence (AI) enabled mobile chatbot psychologist that leverages AIML (Artificial Intelligence Markup Language) and Cognitive Behavioral Therapy (CBT) to provide psychological support. The chatbot is designed to facilitate mental health care by offering personalized CBT interventions to individuals experiencing ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Furthermore, cognitive behavioral therapy has shown promising results in treating anxiety and depression in dementia (Tay et al, 2019 ). LLMs can potentially help administer cognitive behavioral therapy via phone apps (Denecke et al, 2022 ) or in the shape of conversational chatbots (Patel et al, 2019 ; Omarov et al, 2023 ). In an analysis of social media posts on an LLM-powered mental health app (not specifically aimed toward PwD), Ma et al ( 2024 ) reported on-demand and non-judgmental support, the development confidence and self-discovery as the App's benefits.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, cognitive behavioral therapy has shown promising results in treating anxiety and depression in dementia (Tay et al, 2019 ). LLMs can potentially help administer cognitive behavioral therapy via phone apps (Denecke et al, 2022 ) or in the shape of conversational chatbots (Patel et al, 2019 ; Omarov et al, 2023 ). In an analysis of social media posts on an LLM-powered mental health app (not specifically aimed toward PwD), Ma et al ( 2024 ) reported on-demand and non-judgmental support, the development confidence and self-discovery as the App's benefits.…”
Section: Methodsmentioning
confidence: 99%